Branding Kopi Single Origin Kayumas: Upaya Petani Kopi Memasarkan Produk Kopi Arabika Desa Kayumas Situbondo - Sampurna, Insan Cita; Suciati, Luh Putu; Subekti, Sri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The research on the branding of Kayumas single origin coffee as an effort by coffee farmers in Kayumas Village to market Arabica coffee products is intriguing to explore. Despite having the "Java Ijen Raung" single origin certificate, it appears that the brand cannot guarantee the market demand for Arabica coffee from Kayumas Village. This study employs SWOT analysis and QSPM to identify internal and external factors influencing the marketing of Kayumas Arabica Coffee, as well as marketing strategies that should be adopted by Arabica coffee farmers in Kayumas Village. The research results illustrate that Kayumas Arabica Coffee has significant potential for export, but the biggest threat is the lack of support from the local government. Farmers' challenges in marketing their coffee products can be addressed by maximizing opportunities through maintaining product quality and competitive pricing. Promotional efforts can be carried out through both online and offline channels. Online promotion for Kayumas Arabica coffee farmers can be done through platforms like Facebook and Instagram, as well as engaging in sales through e-commerce platforms such as Shopee and Tokopedia. Another solution is to collaborate with relevant institutions to promote the sales of Arabica Coffee.